Expulsion at home for early medical abortion: A systematic review with meta‐analyses. (28th November 2020) - Schmidt‐Hansen, Mia; Pandey, Anuja; Lohr, Patricia A.; Nevill, Michael; Taylor, Peter; Hasler, Elise; Cameron, Sharon
Abstract: Introduction: The safety and acceptability of medical abortion using mifepristone and misoprostol at home at ≤9 +0  weeks' gestation is well established. However, the upper gestational limit at which the procedure remains safe and acceptable at home is not known. To inform a national guideline on abortion care we conducted a systematic review to determine what gestational limit for expulsion at home offers the best balance of benefits and harms for women who are having medical abortion. Material and methods: We searched Embase, MEDLINE, Cochrane Library, Cinahl Plus and Web‐of‐Science on 2 January 2020 for prospective and retrospective cohort studies with ≥50 women per gestational age group, published in English from 1995 onwards, that included women undergoing medical abortion and compared home expulsion of pregnancies of ≤9 +0  weeks' gestational age with pregnancies of 9 +1 ‐10 +0  weeks or >10 +1  weeks' gestational age, or compared the latter two gestational age groups. We assessed risk‐of‐bias using the Newcastle‐Ottowa scale. All outcomes were meta‐analyzed as risk ratios (RR) using the Mantel‐Haenszel method. The certainty of the evidence was assessed using GRADE. Results: Six studies (n = 3381) were included. The "need for emergency care/admission to hospital" (RR = 0.79, 95% confidence interval [CI] 0.45‐1.4), "hemorrhage requiring transfusion/≥500 mL blood loss" (RR = 0.62, 95% CI 0.11‐3.55), patient satisfaction (RR = 0.99, 95% CI 0.95‐1.03), pain (RR = 0.91, 95% CI 0.82‐1.02), and "complete abortion without the need for surgical intervention" (RR = 1.03, 95% CI 1‐1.05) did not differ statistically significantly between the ≤9 +0 and >9 +0  weeks' gestation groups. The rates of vomiting (RR = 0.8, 95% CI 0.69‐0.93) and diarrhea (RR = 0.85, 95% CI 0.73‐0.99) were statistically significantly lower in the ≤9 +0  weeks group but these differences were not considered clinically important. We found no studies comparing pregnancies of 9 +1 ‐10 +0  weeks' gestation with pregnancies of >10 +0  weeks' gestation. The certainty of this evidence was predominantly low and mainly compromised by low event rates and loss to follow up. Conclusions: Women who are having a medical abortion and will be taking mifepristone up to and including 10 +0  weeks' gestation should be offered the option of expulsion at home after they have taken the misoprostol. Further research needs to determine whether the gestational limit for home expulsion can be extended beyond 10 +0  weeks.